Belajardisini : The E-learning Framework Based on Gamification Concept - Pramukantoro, Eko Sakti; Yahya, Widhi (Journal of Information Technology and Computer Science, 2016)
Abstract. The lack of motivation and student engagement in the learning process are the Challenges in education today. E-learning is one of the methods used to resolve these issues.The E-learning, the digital based learning media, enable students to study every where and every time. Basically the e-learning is only used for repository of teaching materials and for evaluation. This kind of e-learning cannot motivateÂ  the learning process. The development of e-learning must be done in order to increase the motivation to learn. The proposed solution extends the e-learning application with the Gamification approach. Gamification is adopted mechanism of the game in non game context. Typically, gamification is used in the business world. The Leaderboard, Challenges, and reward are components that are used to stimulate products sales by marketing. The reward will be given to the top rank salesman on the Leaderboard. This interesting concept can be applied to e-learning to stimulate the learning motivation